2011
DOI: 10.1002/pssc.201000993
|View full text |Cite
|
Sign up to set email alerts
|

Growth and characterization of InGaN for photovoltaic devices

Abstract: In this work we present the growth and characterization of InxGa1–xN‐based materials and solar cells with x up to 0.39. The bandgap of the layers is determined by contactless electroreflectance, which indicates a substantial Stokes shift compared to photoluminescence measurements. Time‐resolved photo‐luminescence was used to confirm the existence of carrier localization phenomenon in the films. Fabricated p‐n devices are then studied for photo‐response under simulated AM0 spectral conditions and under waveleng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…One of the main reasons that InN and GaN are of such interest is because of the ability to modify their electronic properties by alloying them. Herein, Mott-Schottky analysis was used to study the electronic properties of InN, GaN and the composite thin films, a technique which has been previously used in the literature 6265 . The electrical double layer capacitance was measured over a range of applied voltages and the slope of the resulting plot allows one to estimate the carrier concentration of the semiconductor photoelectrodes.…”
Section: Resultsmentioning
confidence: 99%
“…One of the main reasons that InN and GaN are of such interest is because of the ability to modify their electronic properties by alloying them. Herein, Mott-Schottky analysis was used to study the electronic properties of InN, GaN and the composite thin films, a technique which has been previously used in the literature 6265 . The electrical double layer capacitance was measured over a range of applied voltages and the slope of the resulting plot allows one to estimate the carrier concentration of the semiconductor photoelectrodes.…”
Section: Resultsmentioning
confidence: 99%
“…The holes injected to the GaN nanowire LEDs are mostly resided close to the p-GaN region because of large effective mass and low mobility. This nonuniform carrier distribution mainly in the device active region leads to enhance Auger recombination and increase electron overflow [101]. Nguyen et al showed the improvement on hole transport and injection process using the p-doping in the device active region [36].…”
Section: P-type Modulation Doping For the Enhanced Hole Transportmentioning
confidence: 99%
“…The enhanced hole transport also leads to electron overflow reduction, and less Auger recombination [36]. ainly in the device active region leads to enhance Auger recombination and tron overflow [101]. Nguyen et al showed the improvement on hole transport and cess using the p-doping in the device active region [36].…”
Section: P-type Modulation Doping For the Enhanced Hole Transportmentioning
confidence: 99%
“…Research into using In x Ga 1Àx N as an absorber in solar cells is still in its early stages, although a diverse collection of PV device structures has been fabricated and tested including In x Ga 1Àx N p-i-n and p-n homojunction cells, [37,38] In x Ga 1Àx N/Si hetereojunction, [39] In x Ga 1Àx N/GaN heterostructure solar cells with p-n, p-i-n, and nanorod/nanowire configurations, [40][41][42][43][44][45][46]48] In x Ga 1Àx N p-n junctions, [47,49] In x Ga 1Àx N quantum well solar cells, [50][51][52][53][54] and In x Ga 1Àx N quantum dot PV. [55] A comprehensive survey of the current performance of In x Ga 1Àx N-based PV has been compiled by Bhuiyan et al [56] However, In x Ga 1Àx N films with low indium contents have been used commercially for light-emitting diodes (LEDs) in the green, blue, and violet wavelengths and are more technically advanced [57,58] as are In x Ga 1Àx N-based lasers.…”
Section: B Flexibility In Photovoltaic Device Structurementioning
confidence: 99%